The influence of foreign stakeholders on the internationalization strategy of a born global in the health sector - Guerra, Sofia Telles Antunes dos Santos (2018)
The goal of this dissertation thesis is to fill in the gap in the literature regarding the influence of foreign stakeholders in the definition of the internationalization strategy for the health market, more specifically how they influence the definition of the internationalization strategy of a born global company. In order to answer the research question proposed we used qualitative research, specifically a case study approach. After presenting the relevant literature regarding this topic we collected primary and secondary data through interviews and archived internal and external documentation. Through the analyses of the information collected and based upon the theoretical literature, we can conclude that the government is the major stakeholder influencer with regards to the definition of the internationalization strategy of a born global in the health market.